Zapalenie naczyń siatkówki – przyczyny, diagnostyka, leczenie - Brydak-Godowska, Joanna; Dróbecka-Brydak, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Particular types of retinal vasculitis are described and discussed: primary (idiopathic) and secondary to bacterial, viral, fungal, parasite infections and retinal vasculitis coexisting with systemic disease. Symptoms depend on the size and location of the vessels involved. Retinal vasculitis is often accompanied by uveitis.